Responses of soil detachment capacity to different rock dip angles in karst trough valley - Lisha Jiang; Fengling Gan; Xiaohong Tan; Hailong Shi; Youjin Yan; Qiuhao Liao; Junbing Pu (Geoderma)
The karst region is distinguished by pronounced and complex soil erosion, while the bedrock strata dip and root traits significantly influence the erosion slope, thereby altering the hydrodynamic characteristics and impacting Dc. Thus, it is imperative to comprehensively understand the influence mechanism of these factors on Dc in karst trough valley. The samples were collected from two types of natural grassland, Erigeron canadensis (EC; fibrous root system) and Neyraudia reynaudiana (NR; tap root system), as well as bare land (BL) without roots serving as the control. Subsequently, the samples underwent flow scouring in an indoor hydraulic flume at three rock dip angles (15°, 45°, and 65°) and three flow rates (60, 80, and 100 L·min−1) on dip/anti-dip slope. The results indicated that i) the soil organic matter (SOM), water-stable aggregates (WSA), root length density (RLD), root surface area density (RSAD), and root volume density (RVD) on the anti-dip slope were higher compared to those on the dip slope. Additionally, the EC demonstrated the highest abundance in karst trough valley. ii) The Dc of different rock dip angles both dip and anti-dip slopes followed the order of 45° > 65° > 15°. The Dc of two grassland and bare land can be ranked as follows: EC < NR < BL. iii) The Dc of the dip/anti-dip slope showed a significant negative correlation with WSA, root diameter (RD), RLD, RSAD, and RVD (P < 0.05). iv) The results of the multivariate analysis of variance showed that the root traits had the highest contribution rate to Dc, followed by rock dip angles, and bedrock strata dip was the lowest. The resistance of EC to Dc is better under different rock dip angles of the dip/anti-dip slope. Therefore, expanding the coverage of EC across both dip and anti-dip slopes will contribute to mitigating soil erosion and facilitating ecosystem restoration. The research findings enhance the comprehension of soil erosion mechanisms in karst trough valley and facilitate the formulation of effective ecological restoration strategies.